COMPLEX ANALYSIS OF KEY FACTORS OF INFLUENCE ON THE ECONOMIC SECURITY OF ENTERPRISES - PARSHYNA, Olena; PARSHYN, Yurii; NEBABA, Nataliia; STAKHIV, Oleksandr; VESNIN, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents the results of the complex analysis of the systemic impact of key factors on the economic security of enterprises, based on the proposed methodological approach using analytical tools, with the determination of the dynamics of changes and structural shifts. Information base with statistical information for the research based on statistical data for the 14-year period from 2010 to 2023 has been formed. The main trends in the development of domestic enterprises by sectors of the economy during the research have been identified. The presence of negative trends in particular during 2013 – 2014 have been established, which are characterized by a decrease in the volume of products sold (goods, services) of business entities by the type of economic activity. Decrease in the volume of products sold for enterprises in the industrial sector and agricultural enterprises in 2013 has been established. However, more negative impact of factors is being observed at 2022. The highest level of decline at the level of (-93.67%) has been established in the volume of products sold (goods, services) of individual entrepreneurs in 2022. Analysis of the dynamics of sales volumes also allowed us to identify progressive enterprises by the type of economic activity. In particular, positive changes in such types of economic activity as «Wholesale and retail trade; repair of motor vehicles and motorcycles»; «Construction» and «Transport, warehousing, postal and courier activities» based on the results of research on structural shifts that occurred in the period from 2021 to 2023 have been identified. The level of activity of individual entrepreneurs and their role in the development of economic processes during the study has been determined. Imbalances in the process of analytical comparison of the volumes of products sold, in particular, the volumes of products sold by types of economic activity in general at the level of the national economy and by sectors, as well as the volumes of products sold by individual entrepreneurs have been identified. The use of the proposed approach allowed us to determine the systemic impact of key factors and to form the basis for making strategic decisions aimed at ensuring economic security.